News Graph: An Enhanced Knowledge Graph for News Recommendation - Liu, Danyang; Bai, Ting; Lian, Jianxun; Sun, Guangzhong; Zhao, Wayne Xin; Wen, Ji-Rong; Xie, Xing (KARS 2019 - Second workshop on knowledge-aware recommender systems., 2019)
Knowledge graph, which contains rich knowledge facts and well structured relations, is an ideal auxiliary data source for alleviating the data sparsity issue and improving the explainability of recommender systems. However, preliminary studies usually simply leverage a generic knowledge graph which is not specially designed for particular tasks. In this paper, we consider the scenario of news recommendations. We observe that both collaborative relations of entities (entities frequently appear in same news articles or clicked by same users) and the topic context of news article can be well utilized to construct a more powerful graph for news recommendations. Thus we propose an enhanced knowledge graph called [news graph]. Compared with a generic knowledge graph, the news graph is enhanced from three aspects: (1) adding a new group of entities for recording topic context information; (2) adding collaborative edges between entities based on users' click behaviors and co-occurrence in news articles; and (3) removing news-irrelevant relations. To the best of our knowledge, it is the first time that a domain specific graph is constructed for news recommendations. Extensive experiments on a real-world news reading dataset demonstrate that our news graph can greatly benefit a wide range of news recommendation tasks, including personalized article recommendation, article category classification, article popularity prediction, and local news detection.